1982
DOI: 10.1093/infdis/146.6.763
|View full text |Cite
|
Sign up to set email alerts
|

Production of Shigella dysenteriae Type 1-Like Cytotoxin by Escherichia coli

Abstract: Strains of Escherichia coli previously implicated or proven to be causes of diarrhea were examined for production of a toxin similar to that of Shigella dysenteriae type 1 (Shiga). Organisms grown in an iron-depleted broth were lysed by pressure disruption followed by ultracentrifugation. Saline-dialyzed extracts were tested for cytotoxic effects on HeLa cells that were neutralizable with antiserum to Shiga toxin. Among the 13 E. coli strains so analyzed, 11 made a Shiga-like cytotoxin in levels ranging from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
261
1
9

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(282 citation statements)
references
References 31 publications
11
261
1
9
Order By: Relevance
“…The involvement of such factors in the pathogenesis of diarrhoea has been suggested (Scotland et al 1980;Caprioli et al 1983;O'Brien & Laveck, 1983), but it still remains unproven. Our data seem to confirm the role of cytotoxins and hemolysin as virulence factors.…”
Section: Resultsmentioning
confidence: 99%
“…The involvement of such factors in the pathogenesis of diarrhoea has been suggested (Scotland et al 1980;Caprioli et al 1983;O'Brien & Laveck, 1983), but it still remains unproven. Our data seem to confirm the role of cytotoxins and hemolysin as virulence factors.…”
Section: Resultsmentioning
confidence: 99%
“…Many subsequent studies showed that the VT described by Konowa1chuk et al (1977) was virtually identical to the Shiga toxin of Shigella dysenteriae type I (O'Brien et al 1982) first described by Conradi (1903). Subsequently, an antigenically distinct group of toxins with similar biological activity was described by Strockbine et al (1986), who also showed that these toxins are encoded on bacteriophages.…”
Section: Historical Perspectivementioning
confidence: 93%
“…VT+ strains included 20 strains belonging to serotype 0 26 H 11, 2 of serotype 0 26 Hand 2 of 0 128 H2. O'Brien et al (1982) demonstrated the production of VT by EPEC strains of other serogroups when grown in an iron-depleted medium. The significance of these findings has yet to be established.…”
Section: Pathogenesismentioning
confidence: 93%